Психологические основы обучения иностранных студентов языку будущей специальности - Северин, Надежда Васильевна; Криволапова, Елена Владимировна; Квашина, Татьяна Сергеевна (ВД "Гельветика", 2019)
Статтю присвячено дослідженню психологічних основ навчання іноземних студентів мові майбутньої спеціальності. Виділені основні дидактичні принципи цілісного педагогічного процесу, які забезпечують успішне навчання. Розглянута історична ретроспектива питання. З’ясовано, що проблема вивчення психологічних аспектів навчання іноземним мовам постійно цікавить вчених. Її розглядали у своїх працях українські та зарубіжні дослідники. Вчені виділяють чотири групи принципів навчання – лінгвістичні, психологічні, дидактичні та методичні. Метою цієї статті є дослідження психологічних принципів, від реалізації яких значною мірою залежить ефективність процесу навчання мові фаху. Мотивація є незаперечним фактором успішності навчання, особливо в процесі вивчення іноземних мов. Мотив спонукає до діяльності, пов’язаної із задоволенням потреб людини. Дослідники акцентують увагу на розвитку позитивних мотивів, міжпредметних зв’язках як одному з важливих стимулів підвищення інтересу студентів до іноземної мови, виявленні основних видів мотивації та інших питаннях. Урахування психологічних особливостей студентів – мотивів, почуття впевненості в собі, наполегливості у досягненні поставлених цілей, розвитку способів мислення та інших є основою сучасного вивчення іноземних мов. Мотивація відіграє важливу роль у процесі навчання іноземних студентів російській / українській мові. На факультеті міжнародної освіти Національного технічного університету "ХПІ" створено низку навчальних посібників з наукового стилю мовлення, які відіграють важливу роль у навчанні іноземних студентів мові майбутньої спеціальності. Вони призначені для навчання мовам студентів різних спеціальностей – майбутніх інженерів, економістів, лікарів. Навчальний матеріал посібників максимально орієнтований на професійні потреби студентів. Робота з ними здійснюється паралельно викладачами кафедри гуманітарних наук та кафедри природничих наук. Принципи поетапного формування знань та навичок, врахування психологічних особливостей студентів забезпечують максимальну ефективність навчального процесу.

This article is devoted to the study of psychological foundations of teaching Russian to international students. The historical retrospective of the issue is considered. The basic didactic principles of a holistic pedagogical process to ensure successful teaching are highlighted. The problem of studying psychological aspects of teaching foreign languages has been constantly of interest to the scientists. It has been considered in the works of both Ukrainian and foreign researchers. They distinguish four groups of principles of instruction – linguistic, psychological, didactic, and methodical ones. These principles are closely interlinked and ensure successful teaching. The purpose of this article is to consider the psychological principles, implementation of which greatly stipulates the effectiveness of teaching process. Motivation is considered to be the most indisputable factor in success of education in general, especially when learning foreign languages. The motive acts as an incentive for activities related to the satisfaction of human needs. Many researchers focus on the development of positive motives, inter-subject communications as one of the important incentives for increasing students’ interest in a foreign language, as well as identifying the main types of motivation and other issues. Taking into account personal characteristics of students – goals, motivation, self-confidence, persistence in achieving goals, developing ways of thinking and others – form the basis of modern foreign language teaching. Motivation plays an important role in the process of teaching international students the Russian language as a language of future specialty. At the Faculty of International Education of National Technical University “Kharkiv Polytechnic Institute”, there have been created a large number of textbooks on the scientific style of speech. They are intended for teaching Russian to students of various specialties – future engineers, economists, and medics. The educational material of the textbooks is maximally focused on the professional needs of students. The educational activities based on this material are carried out simultaneously by teachers of natural sciences and Russian language teachers. The principles of phased formation of knowledge and skills, taking into account the psychological characteristics of students provide the maximum efficiency of teaching process.
Psychological foundations of teaching international students the language of future specialty
Keywords: дидактические принципы; психологические принципы; мотивация; мотив; языковые компетенции; предметные компетенции; didactic principles; psychological principles; motive; motivation; language competence; subject competence